Urinary Tract Infection and Antibiotic Sensitivity to Culture Most Commonly to Nitrofurantoin and Fosfomycin - Tausif Ahmad, Liaquat Ali Khan, Noorshad Khan, Farman Khan, Ifranullah Khan, Saeed Uddin (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To document susceptibility to Fosfomycin and nitrofurantoin among uropathogens isolated from the OPD and Emergency Room of PAEC General Hospital Islamabad. Material and Methods: The duration of this study was from March 2019 to July 2019, bacteria isolated from urine samples of OPD and emergency room patients suffering from pyuria were evaluated for susceptibility to antibiotic drugs such as nitrofurantoin and Fosfomycin. The medical records of the patients were obtained from hospital record and reviewed for uropathogens and other antimicrobial susceptibilities. The UTIs patients were categorized as complicated and uncomplicated UTIs. Results: This research study enrolled a total of 297 UTI patients with positive urine cultures. Complicated UTIs and uncomplicated UTIs were found in 228 and 69 patients respectively. The Escherichia coli (E. coli) (70.1%) and Klebsiella pneumoniae (15.5%) was the most common pathogens. The susceptibility of E. coli and K. pneumoniae to Fosfomycin and nitrofurantoin was high. Conclusion: The uropathogens in PACE general Hospital Islamabad have higher susceptibilities to antibiotics Fosfomycin than to nitrofurantoin. Keywords: Susceptibility, Urinary Tract Infection, Fosfomycin, Nitrofurantoin, Uropathogens